Gender stereotypes in Portuguese television advertisements - Félix Neto (1998)
This study examined the portrayal of men and women in a sample of Portuguese television commercials, attempting to replicate and extend past investigations none in America, Australia, Britain, and Italy. The aim was to update Portuguese research and to compare findings across cultures. Three hundred and four evening commercials were content analyzed by two raters, one male and the other female, to check reliability. The attributes of each of their central figures were classified into II categories: gender mode of presentation credibility, role, location, age, argument, reward type, product type, background, and end comment. Strong evidence of differences in the presentation of male and female characteristics was obtained The implications of results for the development and maintenance of gender roles are discussed.